A case study of A mesoscale gravity wave in the MLT region using simultaneous multi-instruments in Beijing. (March 2016) - Jia, Mingjiao; Xue, Xianghui; Dou, Xiankang; Tang, Yihuan; Yu, Chao; Wu, Jianfei; Xu, Jiyao; Yang, Guotao; Ning, Baiqi; Hoffmann, Lars
Abstract: In this work, we used observational data from an all-sky airglow imager at Xinglong (40.2 °N, 117.4 °E), a sodium lidar at Yanqing (40.4 °N, 116.0 °E) and a meteor radar at Shisanling (40.3 °N, 116.2 °E) to study the propagation of a mesoscale gravity wave. During the night of March 1, 2011, the imager identified a mesoscale gravity wave structure in the OH airglow that had a wave period of 2 hours, propagated along an azimuthal direction (clockwise) with an angle of 163°, a phase speed of 73 m/s, and a horizontal wavelength of 566 km. Simultaneous measurements provided by the sodium lidar also showed a perturbation in the sodium layer with a 2-hour period. Based on the SABER/TIMED and radar data, we estimated that the momentum flux and the energy flux of the gravity wave were approximately 0.59 m 2 /s 2 and 0.22 mW/m 2, respectively. Ray-tracing analysis showed that the gravity wave was likely generated in the center of Lake Baikal owing to the existence of a jet- front system in the upper troposphere at that time. Highlights: We observed a mesoscale GW in the MLT region using multi-instruments in Beijing. The GW can be observed in both the OH airglow layer and the sodium layer. The wave source is found near Lake Baikal using ray-tracing technique.